Biomaterials for enhancing anti-cancer immunity. (August 2016) - Koshy, Sandeep T; Mooney, David J
Graphical abstract: Highlights: Biomaterials can potentially improve the safety and efficacy of cancer immunotherapy. Biomaterials scaffolds can program immune cell function in peripheral tissues. Lymph node-draining nanoparticles provide potent vaccines. Biomaterial strategies can improve immune cell function within tumors. Abstract : Cancer immunotherapy is becoming a standard approach to treat many cancers. However, shortcomings of current methods limit therapeutic benefit in many patients. Rationally designed biomaterial strategies to deliver immune modulatory drugs can potentially show improved safety profiles, while providing multifunctional and spatiotemporally controlled signals to immune cells to improve their anti-cancer activity. This brief review describes biomaterials-based strategies that enhance immune cell function at various tissue sites to improve anti-cancer immunity. Continued collaboration between bioengineers, immunologists, industry, and clinicians is required for biomaterial-based immunotherapy strategies to continue moving to the clinic.